Evaluation of Dental Students' Perception about Medical Emergencies - Nilvia Maria Lima Gomes; José Henrique de Araújo Cruz; Itamar da Silva Nunes; Isadora da Costa Filgueira; Jamiles Rodrigues Santiago; Julierme Ferreira Rocha; Arthur Willian de Lima Brasil; Julliana Cariry Palhano Freire; Eduardo Dias Ribeiro (Editorial Ciencias Médicas, 2020)
Introduction: Several situations in the dental office may cause emergency cases. Administration of local anesthetics, dental care to patients with systemic deterioration, anxiety and fear are often the most common causes. Objective: To evaluate the dental level of perception of dental students facing the main dental emergencies. Methods: This was a cross-sectional and descriptive study of the data through questionnaires. We interviewed 138 students from the 5th to the 10th period of Dental Medicine at the Federal University of Campina Grande, in the city of Patos, Paraíba. Results: We observed that 86.2% of the interviewed students knew the difference between urgency and emergency; 52.2% of the students confirmed receiving or having received extracurricular instructions about the topic; 59.4% answered that the learning provided about this topic after graduation is not being sufficient. About 17.4% of these students responded positively to knowing how to perform cardiopulmonary resuscitation maneuvers; 11.6% of those interviewed felt themselves prepared to deal with an emergency situation, while 81.9% of the students interviewed intended to seek complementary training during or after graduation. Conclusion: Dental students were found to have a low level of perception about medical emergencies in the dental office.